The Negative Impacts of Suffering on Followership Loyalty Within the Local Church Assemblies in African - ADEYEMI, Paul; ODERINDE, Olatundun; OBASOLA, Kehinde (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Suffering has long been recognized as a central reality in the religious experience of African Christians. The impact of suffering on followership loyalty within the local church assemblies’ remains underexplored. This study investigates the negative effects of suffering on members’ commitment, trust in leadership, and sustained participation in African church contexts. The study adopts a documentation method of content analysis, examining secondary sources such as books and scholarly articles to identify trends and patterns relating to followership loyalty within local church assemblies in Africa. Drawing on theological reflection and sociological insights, the study examines how prolonged economic hardship, unmet spiritual expectations, leadership failure, and unresolved personal crises contribute to disillusionment, reduced engagement and eventual withdrawal from church life. The findings suggest that when suffering is poorly interpreted or inadequately addressed pastorally, it weakens spiritual resilience as well as disrupting faith formation as it erode institutional loyalty. Furthermore, the absence of supportive structures and transparent leadership during periods of suffering intensifies skepticism toward the church and its moral authority. The study concludes by emphasizing the need for contextual pastoral care, sound theological education on suffering, and holistic support systems to restore trust and sustain followership loyalty within African local church assemblies.